2012
DOI: 10.1111/rda.12032
|View full text |Cite
|
Sign up to set email alerts
|

Capabilities and Challenges of Examination of Gene Expression for Quality Assessment of Domestic Cat Embryos

Abstract: Contents Early embryos are characterized by an accurately controlled gene expression pattern that might be deregulated during in vitro culture (IVC). The expression pattern of the developmental genes may serve as markers for embryo quality. Here, we examined the temporal pattern of relative mRNA abundance of genes important for early embryonic development in embryos produced by different fertilization methods [in vitro fertilization (IVF) vs intracytoplasmic sperm cell injection (ICSI)] and sperm sources (fres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Pope et al [ 25 ] were the first to confirm ICSI as a successful method for cat oocyte fertilization with the birth of a live kitten in 1998. Since then, many further studies have been reported [ 1 , 21 , 29 , 49 , 50 , 51 , 52 ] substantiating the applicability of this method for fertilization of fresh oocytes.…”
Section: Discussionmentioning
confidence: 88%
“…Pope et al [ 25 ] were the first to confirm ICSI as a successful method for cat oocyte fertilization with the birth of a live kitten in 1998. Since then, many further studies have been reported [ 1 , 21 , 29 , 49 , 50 , 51 , 52 ] substantiating the applicability of this method for fertilization of fresh oocytes.…”
Section: Discussionmentioning
confidence: 88%
“…For embryos, once again, culture media were designed to resemble the environment where early embryonic development occurs. For cats, one-step [29,59,60] or multi-step [18,19,24,25,[61][62][63][64] IVC systems have been employed. While the former have the advantage of reducing embryo manipulation, while the latter offer the possibility to adapt the nutrient supply according to the developmental stage of the embryos.…”
Section: Culture Mediamentioning
confidence: 99%
“…Investigation on embryo gene expression could also contribute to understand the effects of the in vitro conditions and the specific embryo requirements during IVC. In the domestic cat, it has been proved that gene expression varies according to the embryo stages, and differs between in vitro and in vivo-derived embryos (Filliers et al, 2012), depending also on the culture medium (Hribal, Jewgenow, Braun, & Comizzoli, 2013) and on the spermatozoa status (fresh or cryopreserved; Hribal, Braun, Ringleb, & Jewgenow, 2012).…”
Section: Again the Balance Between Reactive Oxygen Species (Ros) Andmentioning
confidence: 99%